Autotextuality in (In The Presence of Absence) for the poet Mahmoud Darwish. - Tareq Ali Ahmad Al-Sairafy (My University, 2011)
This thesis deals with the theory of autotextuality in Mahmoud Darwish's book In the Presence of Absence, where the poet uses it to autotextualize with him self in the essence, concepts, methods, images, and glossary that serves concepts; which he does in his poetic and prosaic works as well. So, is this autotextuality (or reconstruction of ideas) considered repetition? Or has the poet created his text to avoid repetition? And what has he innovated in this book? This thesis shall answer these questions and others; so I divided it into: an introduction, two chapters, and an epilogue. The introduction sheds light on: the subject, previous studies, the importance of this study, and the methodology I used. In the first chapter, I examined the connection between his above mentioned book- about which the whole study is conducted- and what has proceeded of Darwish's poetry. I traced mutual positions of intertextuality, and found that they meet at many points (i.e. topics), such as: childhood, family relations, immigration and deportation, returning home, occupier and jailor, Palestinian identity, alienation and exile, and sickness and death. I have made these topics as basic titles in my research, and many subtitles have branched accordingly, containing some other textualities. So, I examined them from the perspective of: style, use of pronouns, past and present tense verbs, and imagery. I also referred to the poet's vision of action, or idea, or that of the subject of his poetry; then, that of In the Presence of Absence, which means the time of action, and of the time of writing about it, later on. In the second chapter, I examined the relation between his book, and what has proceeded of the poet's prose: his articles, letters, diaries, and interviews. Thus, I revealed posts of textuality between In the Presence of Absence, and its former prosaic works, as I did in the first chapter. The epilogue contained the most important results I reached after research and examination of this subject; I mainly found: •That Darwish writes many texts on the same subject, but the difference is noticeable in terms of style, glossary, expressions and imagery; thus, there is no repetition. •That he wrote his book depending on memory; which means that he may have forgotten some details of his past life. Especially when he wrote about that early stage of his childhood before Nakba. •That he autotextualizes by drawing images, and reversing analogy sometimes, or even building imagery expressions. •The poet makes great use of external textuality, by repeating it differently in other texts. Consequently, it became part of his culture and language, to create intertextuality.

تتناول هذه الدراسةُ نظريةَ التناصّ الذاتي في كتاب الشاعر محمود درويش (في حضرة الغياب)، إذ إنّ الشاعر في هذا الكتاب يتناص مع ذاته في المضامين والأفكار والأساليب والصور والمفردات التي تخدم الأفكار، وذلك في أعماله الشعرية والنثرية على السواء، فهل يُعدُّ هذا التناص أو إعادة صياغة الأفكار تكرارًا؟ أم أنَّ الشاعر قد أبدع في نصه فاجتنب الوقوع في التكرار؟ وماذا قدم الشاعر في هذا الكتاب من جديد؟ إنَّ هذه الدراسة ستجيبنا عن هذه الأسئلة، وعن غيرها، فقد قمتُ بتقسيم البحث إلى مقدمة وفصلين وخاتمة، بيَّنت المقدمةُ موضوعَ البحث والدراساتِ السابقةَ والمنهجَ الذي سِرتُ عليه. أما الفصل الأول فقد تناولتُ فيه علاقةَ (في حضرة الغياب) بِما سبقه من أشعار درويش، إذْ تتبعتُ مواضعَ التّعالق والتَّناص بينهما، فلاحظتُ أنهما يتناصان بالعديد من الموضوعات مثل: الطفولة، العلاقة الأسرية، الهجرة والترحيل، العودة، المحتلّ، الهويّة الفلسطينية، الغربة والمنفى، المرض والموت. وقد جعلتُ هذه الموضوعاتِ عناوينَ أساسية للمباحث، وقد تفرعتْ منها عناوينُ فرعيةٌ تشتمل على تناصَّات ذاتية، فدرستُ التناص من حيثُ الأسلوب وتوظيف الضمائر والأفعال الماضية والمضارعة، ورسم الصور الفنية، كما أشرتُ إلى رؤية الشاعر إلى الحدث أو الفكرة أو الموضوع في أشعاره، ثم في (في حضرة الغياب)، أي زمن وقوع الحدث، وزمن الكتابة عنه فيما بعد. أما الفصل الثاني فقد درستُ فيه علاقة (في حضرة الغياب) بما سبقه من نثر الشاعر من مقالات ورسائل ومذكَّرات ومقابلات، وكشفتُ عن مواضع التناص بين (في حضرة الغياب) وبين النصوص النثرية السّابقة له، وفعلتُ ما قمتُ به في الفصل الأول. وأما الخاتمة فقد جاءتْ مشتملةً على أهم النتائج التي توصلتُ إليها بعدَ البحث والدراسة في هذا الموضوع، وكانَ من أهم النتائج التي توصلتُ إليها: • أَنَّ درويش يكتب في موضوع ما عدة نصوص، ولكننا نلاحظ الاختلاف فيها من حيث الأسلوب والألفاظ والتعبير والصور، فلا يُعد ذلك تكرارًا. • أنه كتب نصه (في حضرة الغياب) من الذاكرة، وهذا يعني أنه قد ينسى بعض التفاصيل التي مرتْ في حياته، لا سيما أنه كتب فيه عن مرحلة بعيدة من حياته هي مرحلة الطفولة وما قبل النكبة. • أنّه يتناصّ مع ذاته في رسم الصور الفنية مع قلب التشبيهات أحيانًا، أو التغيير في بناء الصورة. • لقد أفاد الشاعر كثيرًا من التناص الخارجي، وبتكراره في نصوصه صار هذا التناص الخارجي جزءًا من ثقافته ولغته، فأصبح تناصًّا ذاتيًّا.
التّناصّ الذّاتي في نصّ (في حضرةِ الغِياب) للشَّاعر محمود درويش